"Image Retrieval Based on Colour, Texture and Shape Feature Similarity Score Fusion Using Genetic Algorithm" - Abhijit T. Somnathe, Dr. S. Ram Reddy (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This paper proposes an image retrieval method based on colour, texture and shape feature similarity score fusion. For checking similarity score we'll use genetic Algorithm. Single feature describes image content only from one point of view, which has a certain limitations. Fusing multifeature similarity score will improve the system's retrieval performance. In this paper, the retrieval results from color, texture and shape feature are analyzed, and the method of fusing multi-feature similarity score is described. For the purpose of assigning the fusion weights of multi-feature similarity scores reasonably, the genetic algorithm is applied. For comparison, other three methods are implemented. They are image retrieval based on color feature, texture feature and fusion of color-texture feature similarity score with equal weights. The experimental results show that the proposed method is superior to other methods.